The Utilization of Mushala in the Development of Islamic Values in Non-Formal Education Environment: A Case Study of Mushola Ar-Rahmah in Salamnunggal Village - Aceng Irfan; Firmansyah; Debi Fajrin Habibi (PT. Pusmedia Group Indonesia, 2025)
This study examines the use of prayer rooms as a means of fostering Islamic values in the context of non-formal education. Prayer rooms serve a strategic role not only as places of worship, but also as centers for educational, spiritual, and social activities. These functions make prayer rooms effective institutions for instilling Islamic values in society. This research aims to: (1) identify the various forms of prayer room utilization in developing Islamic values, (2) analyze the challenges and obstacles faced in optimizing prayer rooms as non-formal education centers, and (3) formulate optimization strategies to enhance the effectiveness of prayer rooms in instilling Islamic values in the community. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation which was carried out at the Ar-Rahmah Mosque, Salamnunggal Village, Cibeber District, Cianjur Regency over a period of three months. The study involved 15 informants consisting of 3 religious leaders, 4 prayer room administrators, 3Madrasah Diniyah administrators, 2 TPQ administrators, and 3 community members, selected through purposive sampling based on their active involvement in prayer room activities. Data analysis was conducted using descriptive analytical techniques through the stages of data reduction, data presentation, and conclusion drawing, with data validity ensured through triangulation of sources and methods. The results of the study show that prayer rooms play a role as a center for fostering Islamic values through various activities such as routine recitation, Qur'an learning, practical worship training, and socio-religious activities. Forms of utilization include the implementation of congregational worship, religious extracurricular activities, and community social development. However, the use of prayer rooms faces obstacles in the form of limited human resources, infrastructure, and low community participation. The optimization strategies needed include the development of varied programs, strengthening organizational management, increasing management capacity, and collaboration with various parties. This research confirms that well-managed prayer rooms can be an effective non-formal education center in forming a generation of faith, noble character, and becoming agents of positive change in society.